2022
DOI: 10.3390/polym14030497
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Openings’ Size and Location on Selected Dynamical Properties of Typical Wood Frame Walls

Abstract: The wooden frame constructions are now popular in many developed countries of the world. Many of these locations where such buildings are constructed are exposed to seismic and other shocks which are generated by human activities. This paper discusses the effect of the size and location of openings in the wooden frame walls under dynamic loadings. Natural frequencies of such frames with and without openings have been determined. Three 14 m high walls with different widths, including 3, 6, and 12 m, have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The frames are usually made from spruce or pine timber surrounded (mostly) by OSB casing and filled with thermal insulation material [ 32 , 33 ]. Szcepanski et al [ 34 ] tested three walls of different widths, with and without two different sizes of openings, in several locations, to monitor the change in their natural frequencies under dynamic loads. The results showed that the effect of the size and location of the openings on the natural frequency is significant (and more sensitive for the location than for the sizes).…”
mentioning
confidence: 99%
“…The frames are usually made from spruce or pine timber surrounded (mostly) by OSB casing and filled with thermal insulation material [ 32 , 33 ]. Szcepanski et al [ 34 ] tested three walls of different widths, with and without two different sizes of openings, in several locations, to monitor the change in their natural frequencies under dynamic loads. The results showed that the effect of the size and location of the openings on the natural frequency is significant (and more sensitive for the location than for the sizes).…”
mentioning
confidence: 99%